UiTM online auction shop / Muhamad Ali Shahid - Shahid, Muhamad Ali (2011)
People continue studies to a higher level to ensure a brighter future. In addition, it also can repay parents who have worked hard to raise their children to be successful in life. Being a student not as easy as thought. To survive as student, wise decision and move is needed in terms of spending money. At the university, textbooks and reference points are scarce and expensive. The problem is, that textbooks purchased; are only used for one or two semester's. After a semester or finished study, it is a time to let go some of items that don't want to bring home or don't want to use anymore. But the items may be useful to other students. In conjunction with green environment campaign, it is better if we can recycle things rather than keep it still in the box or dispose it. Selling these items to other students is a good opinion, but there is no suitable place provided to put advertisement and finding a buyer is not easy. The objective of this project is to design and develop a system that provide place for student to let go some items through online web based application. With this project, student can easily to find seller who want to let go item that still in good condition and also selling unused item to other student who needed. This project will mainly focus on auctioning function such; insert advertisement to be selling, bidding on the items interested, auctioning timer countdown and others. This project will be developing using PHP language and using MySQL as database. As for guideline to complete this project, SDLC waterfall method will be implementing to ensure everything is right on tract. Finally, with the successful of this project is hoped to provide some place for UiTM's student to advertise and market their item so other people who needed can used it.